People skills - Thompson, Neil, 1955- (New York, NY : Palgrave Macmillan, 2015)
"This new edition offers a comprehensive and up-to-date introduction to developing people skills. Written in an accessible and engaging style by leading author Neil Thompson, it is an essential read for students and practitioners of social work and all other helping professions"--
Machine generated contents note: -- PART I: PERSONAL EFFECTIVENESS -- 1. Self-Awareness -- 2. Time Management -- 3. Stress Management -- 4. Information Management -- 5. Assertiveness -- 6. Beating The Bully -- 7. Using Supervision -- 8. Being Creative -- 9. Continuous Professional Development -- 10. Being Realistic And Resilient -- PART II: INTERACTION SKILLS -- 11. Valuing Diversity -- 12. Verbal Communication -- 13. Nonverbal Communication -- 14. Written Communication -- 15. Interviewing -- 16. Influencing Skills -- 17. Leadership -- 18. Handling Feelings -- 19. Managing Conflict -- 20. Multidisciplinary Working -- PART III: INTERVENTION SKILLS -- 21. Anti-Discriminatory Practice -- 22. Being Systematic -- 23. Assessment -- 24. Planning -- 25. Decision Making -- 26. Managing Risk -- 27. Review And Evaluation -- 28. Ending -- 29. Responding To Trauma: Promoting Healing And Recovery -- 30. Reflective Practice.
Includes bibliographical references and index.
Keywords: BUSINESS & ECONOMICS / Management; Interpersonal communication; Interpersonal relations; Problem solving; SOCIAL SCIENCE / Social Work; Self-management (Psychology).